Manual wheelchair's turning resistance: swivelling resistance parameters of front and rear wheels on different surfaces. (3rd April 2021) - Fallot, Constantin; Bascou, Joseph; Pillet, Hélène; Sauret, Christophe
Abstract: Purpose: Daily locomotion with a manual wheelchair includes curvilinear movements. However, little is known about the resisting forces in play during turning manoeuvres where the wheels are generally both rolling and swivelling. This study aimed at quantifying the swivelling resistance parameters of several wheels on different surfaces and to evaluate the effect of the curvature radius on these parameters. Materials and methods: A specific test bench was designed allowing the swivelling resistance parameters of a wheel rolling while swivelling to be determined. Seven wheels (3 front and 4 rear wheels), three surfaces (plywood, linoleum and carpet), two loads (25 and 45 kg) and five curvature radii (from 0 to 0.4 m) were tested through a full factorial design experiment. Results: Results showed that the wheel type was the most influential factor on swivelling resistance parameters, followed by the surface and the curvature radius. The effect of the load on swivelling resistance parameters was found negligible when compared to the influence of other factors. A predictive model for swivelling resistance parameters of the different wheel/surface combinations was proposed, as a function of the curvature radius. Conclusion: This study allowed the swivelling resistance parameters of different wheel/surface combinations to be quantified, as a function of the curvature radius of the wheel trajectory. Combined with data on rolling resistance, these data could now be used to assess energy losses during real life ambulation or to achieve more realistic behaviour in virtual rehabilitation environment. Implications for rehabilitation: Swivelling resistances are increased by carpet surfaces compared to tile surfaces. Conversely to rolling resistance, castors wheels are less prone to swivelling resistance than rear wheels The swivelling resistance of a wheel rolling while swivelling is decreased compared to a pure swivelling movement. Combined with data on rolling resistance, these data on swivelling resistance would allow energy loss during daily life activity to be determined or as input data for the control of wheelchair simulator in virtual environment used for rehabilitation.